Passive leg movement‐induced hyperaemia with a spinal cord lesion: evidence of preserved vascular function. (5th November 2013) - Venturelli, M.; Amann, M.; Layec, G.; McDaniel, J.; Trinity, J. D.; Fjeldstad, A. S.; Ives, S. J.; Yonnet, G.; Richardson, R. S.
Abstract A spinal cord injury (SCI) clearly results in greater cardiovascular risk; however, accompanying changes in peripheral vascular structure below the lesion mean that the real impact of a SCI on vascular function is unclear. Aim Therefore, utilizing passive leg movement‐induced (PLM) hyperaemia, an index of nitric oxide (NO)‐dependent vascular function and the central hemodynamic response to this intervention, we studied eight individuals with a SCI and eight age‐matched controls (CTRL). Methods Specifically, we assessed heart rate (HR), stroke volume (SV), cardiac output (CO), mean arterial pressure (MAP), leg blood flow (LBF) and thigh composition. Results In CTRL, passive movement transiently decreased MAP and increased HR and CO from baseline by 2.5 ± 1 mmHg, 7 ± 2 bpm and 0.5 ± 0.1 L min−1 respectively. In SCI, HR and CO responses were unidentifiable. LBF increased to a greater extent in CTRL (515 ± 41 ∆mL min−1) compared with SCI, (126 ± 25 ∆mL min−1) (P < 0.05). There was a strong relationship between ∆LBF and thigh muscle volume (r = 0.95). After normalizing ∆LBF for this strong relationship (∆LBF/muscle volume), there was evidence of preserved vascular function in SCI (CTRL: 120 ± 9; SCI 104 ± 11 mL min−1 L−1). A comparison of ∆LBF in the passively moved and stationary leg, to partition the contribution of the blood flow response, implied that 35% of the hyperaemia resulted from cardioacceleration in the CTRL, whereas all the hyperaemia appeared peripheral in origin in the SCI. Conclusion Thus, utilizing PLM‐induced hyperaemia as marker of vascular function, it is evident that peripheral vascular impairment is not an obligatory accompaniment to a SCI.